DESAIN BOARD GAME SEBAGAI MEDIA ASERTIF UNTUK MENGURANGI PERILAKU FOMO PADA GENERASI Z: BOARD GAME DESIGN AS AN ASSERTIVE MEDIUM TO MITIGATE FOMO IN GENERATION Z - Naura Nazivah; Fauziah, Emmareta; Arsita Pinandita (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
This board game design addresses the FOMO (Fear of Missing Out) phenomenon among Generation Z, which hinders assertive skills and social interactions. The study aims to create an assertive-interactive medium through qualitative methods (interviews, questionnaires, observations) and SWOT analysis to define the USP (Unique Selling Proposition), strategic positioning, and alignment with Jesse Schell’s 4 Elements of Games (Mechanics, Aesthetics, Story, Technology). The resulting board game incorporates mechanics that encourage self-reflection through storytelling and art therapy via expressive imagery . A fantasy-themed visual design aligns with Generation Z’s interest in supernatural characters, motivating them to confront real-life challenges.